2007
DOI: 10.1080/10790268.2007.11753923
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Use of the Insufflator-Exsufflator in Patients With Spinal Cord injury

Abstract: Background/Objective: The insufflator-exsufflator has been shown to be effective in assisting cough in individuals with spinal cord injury. However, many institutions do not use this device. The study was performed to assess use of the device and attitudes among health care providers. Methods: We developed a questionnaire with 4 categories of questions: knowledge of the device, type of facility, clinical practice with the device, and patient and provider satisfaction. The questionnaire was mailed to members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Compared to the manual cough assist ("quad cough") technique, MIE provides much higher peak expiratory flow (7.47 L/s vs 3.4 L/s). 34 It appears that the use of MIE in individuals with SCI may have been increasing since Bach's article was published in 1993; but in a most recent study by Schimdt, 35 only about 64% of the acute rehabilitation facility was using the MIE device. Given how well the MIE treatment works on secretion management in individuals with acute cervical SCI, the MIE device should be available at all acute rehabilitation facilities that treat individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the manual cough assist ("quad cough") technique, MIE provides much higher peak expiratory flow (7.47 L/s vs 3.4 L/s). 34 It appears that the use of MIE in individuals with SCI may have been increasing since Bach's article was published in 1993; but in a most recent study by Schimdt, 35 only about 64% of the acute rehabilitation facility was using the MIE device. Given how well the MIE treatment works on secretion management in individuals with acute cervical SCI, the MIE device should be available at all acute rehabilitation facilities that treat individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies suggest their efficacy for reducing the number of hospitalizations in chronic patients [47] and for reducing the weaning time [18]. In a survey on the use of MIE, only 49% of the centers that responded acknowledged using the technique routinely [48]. …”
Section: Ventilation Modesmentioning
confidence: 99%
“…A more recent study indicated comparable inpatient usage experience (51%) and somewhat more prevalent (42%) experience using it with outpatients, although the low response rate in that survey (16%) may have biased those findings (12). Patients typically prefer MIE over suctioning (13), and in outpatient settings the treatments are most commonly administered by family members or other caregivers, not nurses (12). Medical complications associated with the use of MIE appear to be rare (14), although barotrauma is a potential concern in some patient populations given the positive pressure associated with the insufflation phase of MIE.…”
Section: Introductionmentioning
confidence: 87%
“…Preliminary results from a survey indicate that most SCI specialists had some inpatient experience with its use; however, only 28% had ever prescribed MIE for outpatient use (11). A more recent study indicated comparable inpatient usage experience (51%) and somewhat more prevalent (42%) experience using it with outpatients, although the low response rate in that survey (16%) may have biased those findings (12). Patients typically prefer MIE over suctioning (13), and in outpatient settings the treatments are most commonly administered by family members or other caregivers, not nurses (12).…”
Section: Introductionmentioning
confidence: 96%